Optimasi Rata - Rata Produksi Ubi Kayu dan Kedelai di Kabupaten Pasaman Barat Menggunakan Pemrograman Kuadratik Metode Wolfe - Nurul Hikmah; Defri Ahmad (UNIVERSITAS NEGERI PADANG, 2022)
This research aims to form a mathematical model in the problem of optimizing the average yield of cassava and soybean yields in West Pasaman Regency based on data from the West Pasaman Statistics Agency from 2007 to 2017 regarding the harvest area and average production of cassava and soybeans. The solution to the average production optimization problem uses the Wolfe's Method of Quadratic Programming. Wolfe method is used using a two-stage simplex iteration. The mathematical model formed is a non-linear equation. The estimation of parameters in the mathematical model uses the least squares method, which is calculated using the Matlab software. Optimization results using the Wolfe Method Quadratic Programming obtained an average of 340.95 kw / ha of cassava and soybeans, with an optimal harvest area of 255.38 ha of cassava and 469.5 ha of soybean harvest area.